(untitled) (Heritage, 2026)
In the paper, the author deals with creating a connection between the preamble of the Serbian Constitution of 2006 and the concept of constitutional identity, in the part where the preamble mentions Kosovo and Metohija. In the first part, he deals with the origin and concept of the preamble, while in the second part, its legal nature is determined. Then, he points out the problems of the part of the preamble that refers to Kosovo and Metohija. Finally, the author, explaining the concept and importance of constitutional identity, makes a connection between Kosovo and Metohija in the preamble and the constitutional identity of our country, and concludes that the intention of the framers of the constitution was probably to "carve" Kosovo and Metohija into our constitutional identity.